2022
DOI: 10.3389/fpsyg.2022.1005709
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of internal cohesion psychotherapy in treating young clients with depression and anxiety disorders: The role of developmental assets in Kosovo context

Abstract: The positive youth development approach (PYD) is widely used as a meaningful framework to guide research, policy, and intervention, to support young people to develop their full potential. Psychotherapy, on the other hand, is a verbal and psychological procedure that can be a suitable solution to mental health concerns, which are prevalent among youth. This study aimed to explore the potential role of developmental assets in treating clients with depression and anxiety disorders using Internal Cohesion Psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…A quantitative study with a large sample (N = 853) provided evidence upon which the principles of ICP were created. The results of this study, which used different structural equation models and was originally published by Uka et al (2022), showed significant bidirectional associations between intrapersonal, interpersonal, professional and spiritual systems. Moreover, results confirmed that the past has a significant effect on the present and the future, and the present also has a significant effect on the future.…”
Section: An E Viden Ce-ba S Ed Psychother Apy Approachmentioning
confidence: 75%
See 3 more Smart Citations
“…A quantitative study with a large sample (N = 853) provided evidence upon which the principles of ICP were created. The results of this study, which used different structural equation models and was originally published by Uka et al (2022), showed significant bidirectional associations between intrapersonal, interpersonal, professional and spiritual systems. Moreover, results confirmed that the past has a significant effect on the present and the future, and the present also has a significant effect on the future.…”
Section: An E Viden Ce-ba S Ed Psychother Apy Approachmentioning
confidence: 75%
“…A recent study by Uka et al (2022) confirmed the effectiveness of ICP in treating depression and anxiety. Practicability, simplicity and structure were appraised among the main qualities of ICP by clients who received treatment using this approach.…”
Section: An Integ R Ative Approach Aiming For Internal Cohe S Ionmentioning
confidence: 88%
See 2 more Smart Citations
“…The core components of ICP approach are systems (intrapersonal, interpersonal, professional and spiritual) and three-time perspectives (client's past, present and future). Systems are composed of client's important relations, which are interrelated with one another and dependent on the construct of time [10]. Therefore, during ICP intervention, the therapist guides the client to go through the important events in the past, the current experiences, thoughts, and feelings as well as future plans related to each system.Recent evidence [9] confirmed the effectiveness of ICP in treating depression and anxiety with the clients who received treatment appraising practicability and simplicity as main ICP values.…”
mentioning
confidence: 99%